STUDI TEKNOLOGI ALAT TANGKAP JARING SEMBILANG YANG MENGGUNAKAN TUASAN DI DESA PEMATANG SEI BARU KECAMATAN TANJUNG BALAI ASAHAN KABUPATEN ASAHAN PROVINSI SUMATERA UTARA - Andriani, Hanny; Brown, Arthur; Rengi, Pareng (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
This research was conducted in October 2013 in Pematang Sei Baru village of Tanjung Balai Asahan sub regency Asahan Regency in North Sumatera Province. This study aims to determine the level of environmental friendly sembilang gillnet using Fish Aggregating Device (Tuasan) or FAD and economical feasibility of this environmentally friendly technologies. The method used in this study is a survey method with direct observation both interviews and discussions with fisherman. Observation by using FAO (1995) criteria shows that this fishing gear in combination with FAD could be classified into environmentally friendly fishing gear. The results of the feasibility analysis calculations indicate that this gillnet bussiness proved provide benefits for fishermen and deserves to be developed because of the value of BCR (Benefit Cost Ratio) retrieved of 3.07; FRR (Financial Rate of Return) is 181.91% and PPC (Payback Period of Capital) is only 6 months and 18 days.